Consistency rates of clinical and histopathologic diagnoses of oral soft tissue exophytic lesions - Javad Sarabadani; Maryam Ghanbariha; Saeedeh Khajehahmadi; Masoumeh Nehighalehno (Tabriz University of Medical Sciences, 2009)
Background and aims. Histpathologic diagnosis of exophytic lesions is occasionally influenced by clinical and radiographic diagnosis and even the surgeon's observation during biopsy. The aim of this study was to evaluate the cases with failure in clinical diagnosis.
Materials and methods. A total of 73 patients with peripheral exophytic lesions were evaluated in Zahedan Faculty of Dentistry in 2006. Specialists gave their differential diagnoses based on the criteria of oral medicine texts. Then a biopsy was taken and the histopathologic diagnosis was determined. Finally, consistency rates of clinical and histopathologic diagnoses were determined. Statistical analysis was carried out with SPSS software using Chi-Square and Fisher's exact tests.
Results. In the present study 73 subjects with oral soft tissue (peripheral) exophytic lesions were orally examined and biopsies were taken. Forty-four subjects (60.35%) were females and 29 (39.7%) were males. A total of 81.7% (62 subjects) of clinical diagnoses were consistent with histopathologic reports. In 18.3% (11 subjects) of the cases clinical diagnoses were not confirmed by histopathologic reports.
Conclusion. In order to reach a diagnostic agreement, conformity of clinical and histopathologic diagnoses is necessary.